Pancheshwar Multipurpose Project: Nepal’s Portion of Water - Pun, S. B. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
On September 20, 1996 an overwhelming 96.5% of the members present at the Joint Session of the Nepalese Parliament hurriedly ratified the Mahakali Treaty to fulfill the requirements of Article 126 of the 1990 Constitution of Nepal.The then Prime Minister Sher Bahadur Deuba and Water Resources Minister Pashupati SJB Rana provided CPN-UML General Secretary Madhav Kumar Nepal and CPN-UML Mahakali Study Team Coordinator KP Sharma (Oli) written replies on the “equal sharing” of the Mahakali waters. However, despite the lapse of 15 years, the two critical clauses: i) “...equal entitlement in the use of Mahakali waters without prejudice to their respective consumptive uses...,” and ii) “...precludes the claim, in any form, by either Party on the unutilized portion of the shares of the waters...” still remain obfuscated and clouded in mist. Is “equal entitlement” (50 percent each) considered after deducting the respective consumptive uses as interpreted but later withdrawn by Minister Rana? Or is this “equal entitlement” (50 percent each) considered prior to deducting the consumptive uses as interpreted by Secretary General MK Nepal and then applying the clause “without prejudice” to their respective consumptive uses? No attempts appear to have been made by Nepal to elicit the Government of India’s interpretations on this vital issue. The Ganges basin supports a massive over 523 million people; i.e., 450 million in India, 45 million in Bangladesh, and 28 million in Nepal. With India’s economy growing consistently at a high 8 to 9% annually, the quality of life of her people is definitely on the rise. This will invariably mean drastic increases in her per capita consumption of water. With Nepal contributing over 72% of the dry season flows of the Ganges, India’s eyes and ears are on Nepal either in the form of “...without prejudice to their respective consumptive uses...” or “...precludes the claim, in any form, ...the unutilized portion of the waters...” However, Nepalese governments from the Panchayat era perceived water, whether by design or otherwise, as a mere secondary component of hydropower. Despite the full knowledge that water has become a scarce diminishing resource, the Nepalese Governments continue to be mesmerized by hydropower. This is manifested by the government unveiling in a span of two years her grand dreams of 10,000 MW in ten years and 25,000 MW in twenty years. This article attempts to delve into the intricacies of the Mahakali waters as expounded by Prime Minister SB Deuba’s government during the extremely hurried ratification the Mahakali Treaty in 1996. DOI: http://dx.doi.org/10.3126/hn.v8i0.4925 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 48-56 Uploaded date: 23 June, 2011